PERSEPSI DAN SIKAP IBU TERHADAP KLAIM GIZI DALAM IKLAN SUSU FORMULA LANJUTAN ANAK USIA PRASEKOLAH DAN HUBUNGANNYA DENGAN KEPUTUSAN PEMBELIAN - Hidayat, Inna Kurnia; Sumarwan, Ujang; Yuliati, Lilik Noor (Jurnal Ilmu Keluarga dan Konsumen, 2009)
Not all advertisements give correct information, therefore make the consumer confuse. The aimed of this research were to analyze category of advertisement claim, purchasing decision and the relationship of individual characteristics and mother’s perception, the relationship of perception and attitude towards nutritional claim, the relationship of perception and attitude of nutritional claim on advertisement of formula milk for pre-school children and purchasing decision. There was a positive significant correlation between per capita income with perception. Perception towards claim positively and significantly correlated with the influenced grade of nutritional claim. In other hand, attitude towards claim had a negative significant correlation with the influenced grade of nutritional claim. There was a positive significant correlation between attitude towards claim with buying frequency. There was a positive significant correlation between perception and attitude towards claim with the period of formula milk brand usage.